The Argentinian experience with yerba mate in agroforestry - Colcombet, Luis; Gonzalez, Paola Analia; Barth, Sara Regina; Beltran, Marcelo Javier; Arndt, Guillermo Martin (Tropenbos International, 2024)
Climate change mitigation and food security are two of the main challenges in today’s societies. Agroforestry — defined as the presence of trees on cropland, as external and internal boundaries and on any other available niche of farmland — can provide both food and climate change mitigation. As an agroecosystem that combines trees with farming practices, agroforestry has the potential to increase both biomass and soil carbon while maintaining agricultural production (Cardinael et al. 2017). There are several types of agroforestry systems, with different rates of above-ground and soil carbon sequestration (Corbeels et al. 2019). Agroforestry also contributes to water quality improvement, biodiversity enhancement, erosion control and nutrient cycling and availability (Dordel 2009; Varah et al. 2013)